Assessing the service quality at health service facilities during the COVID-19 pandemic in North Buton District, Indonesia - Ahmad, La Ode Ali Imran; Akbar, Muhammad Ikhsan; Nurmaladewi, Nurmaladewi; Aspian, Pitrah; Pagala, Iriyanto; Rustam, Muhammad (Public Health of Indonesia, 2022)
Background: The degree of quality health is greatly influenced by existing health services. Thus, assessing the service quality during the COVID-19 pandemic is necessary. Objective: This study aimed to describe the quality of services in health service facilities in North Buton District during the pandemic. Method: A descriptive survey research was conducted in 2021. A total of 400 respondents were selected using accidental sampling. Data were analyzed using descriptive statistics and presented in the form of frequency distribution tables and narratives. Results: The quality of service (tangible, reliability, responsiveness, assurance, and empathy) was sufficient. Changes in the quality of health services were more likely related to changes in service flow and operating hours. However, although the service quality was adequate, some respondents (8% to 12%) complained about unavailability of hand sanitizer in the waiting room, inadequate detailed information related to COVID-19, slow registration process, lack of medical personnel, and less friendly healthcare workers. Conclusion: This study may serve as input for health policymakers and hospital and public health center managers to improve health service quality.